Magnetohydrodynamic Oscillatory Free Convection from a Vertical Plate - Prasad Mishra, Shankar; Charan Muduli, Jugal (Engineering Transactions, 1976)
This paper investigates the problem of oscillatory free convection laminar boundary layer flows from a semi-infinite vertical flat plate in the case when the mean surface-temperature varies as a function of the distance from the leading edge and there is a transverse magnetic field imposed at the plate. The induced magnetic field and the viscous dissipation term have been neglected and the study of the oscillatory flow is restricted to a small amplitude only.